If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -0.8(x + -4) = 0.4(9x + -4) Reorder the terms: 12 + -0.8(-4 + x) = 0.4(9x + -4) 12 + (-4 * -0.8 + x * -0.8) = 0.4(9x + -4) 12 + (3.2 + -0.8x) = 0.4(9x + -4) Combine like terms: 12 + 3.2 = 15.2 15.2 + -0.8x = 0.4(9x + -4) Reorder the terms: 15.2 + -0.8x = 0.4(-4 + 9x) 15.2 + -0.8x = (-4 * 0.4 + 9x * 0.4) 15.2 + -0.8x = (-1.6 + 3.6x) Solving 15.2 + -0.8x = -1.6 + 3.6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.6x' to each side of the equation. 15.2 + -0.8x + -3.6x = -1.6 + 3.6x + -3.6x Combine like terms: -0.8x + -3.6x = -4.4x 15.2 + -4.4x = -1.6 + 3.6x + -3.6x Combine like terms: 3.6x + -3.6x = 0.0 15.2 + -4.4x = -1.6 + 0.0 15.2 + -4.4x = -1.6 Add '-15.2' to each side of the equation. 15.2 + -15.2 + -4.4x = -1.6 + -15.2 Combine like terms: 15.2 + -15.2 = 0.0 0.0 + -4.4x = -1.6 + -15.2 -4.4x = -1.6 + -15.2 Combine like terms: -1.6 + -15.2 = -16.8 -4.4x = -16.8 Divide each side by '-4.4'. x = 3.818181818 Simplifying x = 3.818181818
| 5(24+16)-9=-8(5y-45) | | 12x-(2x-12)=4+9x | | 11=-4x-9 | | -3p-3=-9-2p | | 2(x+4)=x+8 | | 2(x+4)=2x-8 | | 2(x+4)=x-8 | | 3(d-9)=4(d-5) | | 5x/2-x=x/10-21/5 | | 6(2z-3)+3z=22 | | 34+21= | | 6x+4x+3+8=5x+3+4x | | 6-8(a+1)=7+a | | 11111-1532= | | 4x+12=2X+2 | | (21b-9)-5(4b+1)=-7 | | 4x+12=2X+1 | | (21b-9)-5(4+1)=-7 | | 23.5a+12.5=9.3a-4.8 | | g(x)=2x^2+x-1 | | 3p-5=-8 | | =2+14+88/22*9+12-6-8 | | 2*x+18=0 | | -16k^2+8k+24=0 | | 42=-3(m+6)+m | | y^3-13y^2+40y= | | y-18=9 | | 2x^2-19x=0 | | 7=10(y-8) | | p=30x+40y | | x-3x=10 | | 9=-7(w-4) |